2001
DOI: 10.1053/euhj.2000.2545
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced external counterpulsation improved myocardial perfusion and coronary flow reserve in patients with chronic stable angina. Evaluation by13N-ammonia positron emission tomography

Abstract: Enhanced external counterpulsation therapy improved myocardial perfusion at rest and with dipyridamole and was associated with an increased exercise tolerance with(13)N-ammonia positron emission tomography and increased nitric oxide levels. These results suggest that one of the enhanced external counterpulsation mechanisms is development and recruitment of collateral vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 19 publications
7
114
1
5
Order By: Relevance
“…measured directly. 7 More recently, Bonetti et al did demonstrate an improvement in peripheral endothelial function that persisted up to 1 month after treatment. 8 Although related to endothelial function, arterial stiffness may vary in an endothelial-independent manner in different subjects.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…measured directly. 7 More recently, Bonetti et al did demonstrate an improvement in peripheral endothelial function that persisted up to 1 month after treatment. 8 Although related to endothelial function, arterial stiffness may vary in an endothelial-independent manner in different subjects.…”
Section: Discussionmentioning
confidence: 94%
“…23 On the other hand, several studies have demonstrated increased myocardial perfusion with associated release of endothelial growth factors, improved coronary endothelial function, and decreased neurohumeral factors, which may reflect improved ventricular hemodynamics. 3,[5][6][7] Hence, the bulk of the evidence to date suggests that EECP exerts its sustained clinical benefits through improvements in cardiac status, rather than benefitting the peripheral vascular system. Our study result supports this theory by failing to demonstrate any measurable change in central or peripheral arterial stiffness immediately or 4 months post completion of EECP therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Objective measures of coronary ischaemia have demonstrated improved time to ST-segment depression, stress myocardial perfusion, 16 and PET scan myocardial perfusion at rest and after dipyramidole. 17 Benefits have been demonstrated to be durable in many patients for up to five years after treatment. 18 Extracorporeal shock wave therapy Another proposed treatment for patients with severe coronary artery disease with no options for PCI or surgery is extracorporeal cardiac shock wave therapy (ECST).…”
Section: Enhanced External Counterpulsationmentioning
confidence: 99%